New insights into the characteristics of DRAK2 and its role in apoptosis: From molecular mechanisms to clinically applied potential - Youwei Zheng; Xinchao Li; Lirun Kuang; Yong Wang (Frontiers Media S.A., 2022)
As a member of the death-associated protein kinase (DAPK) family, DAP kinase-associated apoptosis-inducing kinase 2 (DRAK2) performs apoptosis-related functions. Compelling evidence suggests that DRAK2 is involved in regulating the activation of T lymphocytes as well as pancreatic β-cell apoptosis in type I diabetes. In addition, DRAK2 has been shown to be involved in the development of related tumor and non-tumor diseases through a variety of mechanisms, including exacerbation of alcoholic fatty liver disease (NAFLD) through SRSF6-associated RNA selective splicing mechanism, regulation of chronic lymphocytic leukemia and acute myeloid leukemia, and progression of colorectal cancer. This review focuses on the structure, function, and upstream pathways of DRAK2 and discusses the potential and challenges associated with the clinical application of DRAK2-based small-molecule inhibitors, with the aim of advancing DRAK2 research.